2017
DOI: 10.18632/oncotarget.23451
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, follow-up, and treatment of urethral recurrence following radical cystectomy and urinary diversion for bladder cancer: a meta-analysis of 9498 patients

Abstract: PurposePatients frequently undergo radical cystectomy and urinary diversion for treatment of bladder cancer. However, they remain at risk of urethral recurrence (UR). Studies have determined various risk factors leading to urethral recurrence. However, no publications have weighed the predictive values of these factors.Materials and MethodsStudies published between 1971 and 2016 were retrieved from PubMed, EMBASE and MEDLINE. We used STATA software (Version 12.0) to estimate the pooled risk ratio.ResultsTwenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
0
15
1
2
Order By: Relevance
“…The procedure involves removal of the entire bladder, lymph nodes, part of the urethra, and nearby organs that may contain cancer cells. Still, patients after RC remain at risk of BC recurrence with remaining urethra as a common recurrence site 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The procedure involves removal of the entire bladder, lymph nodes, part of the urethra, and nearby organs that may contain cancer cells. Still, patients after RC remain at risk of BC recurrence with remaining urethra as a common recurrence site 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with this finding, in a large-scale study involving 6,169 patients, HR of CIS for UR was 0.97 (p=0.88). 4 However, in a large meta-analysis of 9,498 patients, 21 BC patients with CIS showed a higher probability of developing UR than patients without CIS (RR = 3.09; 95% CI: [1.48, 6.47]), which may be attributed to the inclusion of female patients in this meta-analysis.…”
Section: Discussionmentioning
confidence: 81%
“…20 Conversely, another study reported higher UR rate in low-stage than high-stage tumors. 21 On the other hand, Kang Su Cho demonstrated that tumor stage is not an independent risk factor of UR. 18 These discrepancies may be ascribed to that there are no pT1 stage patients and only male patient included in our study.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical cystectomy with urinary diversion is the method of choice for the treatment of muscle- invasive bladder cancer. [ 1 ] In these cases, urinary diversion is achieved by the reconstruction of an orthotopic neobladder or an ileal conduit. [ 2 ] Transitional cell carcinoma, the most common pathological type of bladder carcinoma, is defined as a pan-urothelial disease characterized by recurrent and multifocal metachronous tumors of urinary organs.…”
Section: Introductionmentioning
confidence: 99%